Social representations on visualization of old age and the concepts of old man, old woman, old adult in high school students in Guadalajara, Jalisco - Almejo Vargas, Juan Ramón (2022)
Objective: To know the social representations of high school students regarding the concepts of old, old and elderly and their future visualization of their old age. Method: Population 37 high school students, study with qualitative approach, Social Representations design, free listing technique, electronic questionnaire elaborated with Google forms, processual and prototypical analysis. Results: Female sex prevailed (57%), the age range was 16 years (60%), the school grade was second year (54%). The perception of the concepts was positive (35%). The future visualization of old age was positive (81%). The central nuclei of the SRs of the concepts were: old, family, wrinkles, great, experience, tender, wise, gray hair, and the visualization of old age were: happy, traveling, gray hair, cheerful, healthy, grandchildren and wrinkles. Conclusions: Concepts and visualization of old age possess positive RS, intergenerational coexistence and economic status have positive influence.